Mapping Danish Research on Research and Innovation - Degn, Lise; Bloch, Carter Walter; Schneider, Jesper Wiborg (CFA Scientific Reports, 2015)
This report presents the results of a study aimed at mapping Danish research on research and innovation (RI-research). The study was conducted by the Danish Centre for Studies in Research and Research Policy, Aarhus University, from December 2013 to September 2014, for the Danish Agency for Science, Technology and Innovation, under the Ministry of Higher Education and Science. The report contains results and analyses based on five interconnected parts of the study: (1) desk research providing an initial overview of a diverse field and a working definition of RI-research; (2) a survey among department heads addressing the resources and organization of RI-research; (3) a co-nomination study among researchers in the field mapping the cognitive networks and cooperation patterns; (4) qualitative interviews with key researchers in the field; and (5) bibliometric analyses of the impact of Danish RI-research.